Determinants of pain interference and headache impact in patients who have chronic migraine with medication overuse: Results from the MOTS trial. (September 2021) - Schwedt, Todd J; Sahai-Srivastava, Soma; Murinova, Natalia; Birlea, Marius; Ahmed, Zubair; Digre, Kathleen; Lopez, Kristina; Mullally, William; Blaya, Maike Tiede; Pippitt, Karly; Cutrer, Fred Michael; DeLange, Justin; et al.
Objective: "Pain interference" and "headache impact" refer to negative consequences that pain and headache have on one's life. This study investigated determinants of these negative impacts in a large patient cohort who have chronic migraine with medication overuse. Methods: Six hundred and eleven adults were enrolled from 34 headache, neurology, and primary care clinics. Negative consequences of chronic migraine with medication overuse were determined using the Patient-Reported Outcomes Measurement Information System (PROMIS) Pain Interference 6b questionnaire and the Headache Impact Test 6. Relationships between PROMIS-6b and Headache Impact Test 6 scores with demographics, headache characteristics, medication use, anxiety symptoms, and depression symptoms were assessed with linear regression. Elastic Net regression was used to develop a multiple regression model. Results: PROMIS-6b T-Scores averaged 65.2 (SD 5.4) and Headache Impact Test 6 scores averaged 65.0 (SD 5.3), indicating severe negative consequences of chronic migraine with medication overuse. Chronic migraine with medication overuse interfered with enjoyment of life, concentration, daily activities, doing tasks away from home, and socializing. Depression symptom severity had the strongest relationship with pain interference and headache impact. Moderate-to-severe headache frequency, headache intensity, and anxiety symptoms were also associated with pain interference and headache impact. Conclusions: Chronic migraine with medication overuse is associated with substantial negative consequences, the extent of which is most strongly related to depression symptoms.